Analysis of risk factors affecting the HIV epidemic process in the penitentiary system - S. E. Kondratova; A. N. Marchenko (Журнал микробиологии, эпидемиологии и иммунобиологии, 2022)
Introduction. For more than 10 years, the Tumen Region has been reporting steadily high rates of HIV infection prevalence. Among the groups at risk for HIV infection, a special place is occupied by the group of incarcerated individuals. This group is mostly represented by drug users, men who have sex with men, commercial sex workers. Diseases acquired during imprisonment or exacerbated in a prison setting become a problem not only for released inmates, but also for communities outside the prison system. Epidemiologically, it is critically important to identify the prison-related factors contributing to HIV progression, considering their unequal significance among incarcerated individuals and civilian population.